Bowel strangulation caused by massive intraperitoneal adhesion due to effective chemotherapy for multiple peritoneal metastases originating from descending colon cancer - Horii, Nobutoshi (Clin J Gastroenterol, 2016)
We describe a case of bowel strangulation caused by massive peritoneal adhesion as a result of effective chemotherapy. A 71-year-old man, who had obstructive descending colon cancer with massive peritoneal metastases and, therefore, received palliative surgery consisting of diverting colostomy and sampling of peritoneal nodules, developed bowel strangulation on day 4 of the 2nd course of chemotherapy, including irinotecan, l-leucovorin, and 5-fluorouracil. Emergent celiotomy showed a massive intraperitoneal adhesion formed around several intestinal loops, which were not observed at the prior surgery. One loop was strangled, but recovered by adhesiotomy alone. Intestinal loops were formed around aggregates of peritoneal nodules as the centers, several of which were then sampled. We closed the abdomen after all intestinal loops were eradicated by total enterolysis. Fortunately, the patient has been doing well and received chemotherapy without recurrent bowel obstruction 10 months after the present episode. Histological findings of the aggregates causing intestinal loops demonstrated extensive necrosis of cancerous tissue surrounded by fibrosis with abundant lymphocyte infiltration. These findings were not observed in the specimen sampled before chemotherapy, suggesting that intestinal loops were caused by inflammatory adhesion occurring around the peritoneal metastases as a result of effectiveness of chemotherapy.